A review on contribution of transgenic paddy (Oryza sativa L.) towrads enhancing nutritional value / Nurul Ain Nadirah Mahmud - Mahmud, Nurul Ain Nadirah (Faculty of Plantation and Agrotechnology, 2016)
This literature review is to determine the relationship between the growing population with the rice production demand, and micronutrient malnutrition rate. Micronutrient malnutrition refers to the condition where individual unable to intake sufficient amount of macronutrients that compose largely of Vitamin A, Iron and Vitamin B9 and do not show obvious symptoms (Ruel-Bergeron et ai., 2015). Micronutrient malnutrition severely affects both in under develop and developing countries. This incident occurs due to the expensive prices of vegetables and fruits, and low accessibility to obtain the nutritious vegetables and fruits compare to the high incomers, but micronutrients malnutrition also effect overweight children due to the unbalance food consumption that largely cause by salt, sugar, and addictive flavor. Several approaches like pharmaceutical supplementation, industrial food fortification, and diet diversification did help in reducing the micronutrient malnutrition problems but all the approaches success on the minimum rate. Thus, the research and development of transgenic rice rich essential micronutrients through bio-fortification method is another novel strategy to combat off the micronutrient malnutrition. Rice is a low micronutrients - major staple crop for almost half of the world population especially in under develop and developing countries. Even though, the rice production of 1st generation of transgenic rice with high yielding output increase over the year, but it is still not enough to deliver enough intake of needed essential micronutrients. Then, the 1st generation of transgenic rice shifts to the 2nd generation of transgenic rice which are more consumers - friendly focusing on the nutritional value enhancement on the edible rice endosperm. The method of elevating the nutrition content is focusing on the rice endosperm; the edible part of the rice plant breaks the inefficient previous methods of pharmaceutical supplementation, industrial food fortification and diet diversification.